Respostas
respondido por:
1
a)
![y = x + 3 \\ y = 2x + 6 \\ x + 3 = 2x + 6 \\ 2x - x = 3 - 6 \\ x = - 3 \\ \\ y = x + 3 \\ y = - 3 + 3 \\ y = 0 y = x + 3 \\ y = 2x + 6 \\ x + 3 = 2x + 6 \\ 2x - x = 3 - 6 \\ x = - 3 \\ \\ y = x + 3 \\ y = - 3 + 3 \\ y = 0](https://tex.z-dn.net/?f=y+%3D+x+%2B+3+%5C%5C+y+%3D+2x++%2B+6+%5C%5C+x+%2B+3+%3D+2x+%2B+6+%5C%5C+2x+-+x+%3D+3+-+6+%5C%5C+x+%3D++-+3+%5C%5C++%5C%5C+y+%3D+x+%2B+3+%5C%5C+y+%3D++-+3+%2B+3+%5C%5C+y+%3D+0)
b)
![2x + y = 7 \\ y = 7 - 2x \\ \\ x + 3y = 11 \\ x + 3(7 - 2x) - 2x = 11 \\ x + 21 - 6x - 2x = 11 \\ - 7x = 11 - 21 \\ 7x = 10 \\ x = \frac{10}{7} \\ \\ y = 7 - 2x \\ y = 7 - 2 \times \frac{10}{7} \\ y = 7 - \frac{20}{7} \\ \frac{7y}{7} = \frac{49}{7} - \frac{20}{7} \\ 7y = 39 \\ y = \frac{39}{7} 2x + y = 7 \\ y = 7 - 2x \\ \\ x + 3y = 11 \\ x + 3(7 - 2x) - 2x = 11 \\ x + 21 - 6x - 2x = 11 \\ - 7x = 11 - 21 \\ 7x = 10 \\ x = \frac{10}{7} \\ \\ y = 7 - 2x \\ y = 7 - 2 \times \frac{10}{7} \\ y = 7 - \frac{20}{7} \\ \frac{7y}{7} = \frac{49}{7} - \frac{20}{7} \\ 7y = 39 \\ y = \frac{39}{7}](https://tex.z-dn.net/?f=2x+%2B+y+%3D+7+%5C%5C+y+%3D+7+-+2x+%5C%5C++%5C%5C+x+%2B+3y+%3D+11+%5C%5C+x+%2B+3%287+-+2x%29+-+2x+%3D+11+%5C%5C+x+%2B+21+-+6x+-+2x+%3D+11+%5C%5C++-+7x+%3D+11+-+21+%5C%5C+7x+%3D+10+%5C%5C+x+%3D++%5Cfrac%7B10%7D%7B7%7D++%5C%5C++%5C%5C+y+%3D+7+-+2x+%5C%5C+y+%3D+7+-+2+%5Ctimes++%5Cfrac%7B10%7D%7B7%7D++%5C%5C+y+%3D+7+-++%5Cfrac%7B20%7D%7B7%7D++%5C%5C++%5Cfrac%7B7y%7D%7B7%7D++%3D++%5Cfrac%7B49%7D%7B7%7D++-++%5Cfrac%7B20%7D%7B7%7D++%5C%5C+7y+%3D+39+%5C%5C+y+%3D++%5Cfrac%7B39%7D%7B7%7D+)
b)
MarianaAvelino20:
Valeu cara,me ajudou muitíssimo!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás